Rola etosu w kształtowaniu działań społecznie odpowiedzialnych w świetle przeprowadzonych badań - Kapias, Michał; Polok, Grzegorz (Annales. Etyka w Życiu Gospodarczym, 2015)
The subject of responsibility has lately become very important in the context ofthe economic crisis. In economy, it took the form of social responsibility. It concernsactivities additionally undertaken by organizations in order to establish correctrelations with their employees and society, as well as with regard to the naturalenvironment.Therefore, a very important role is played by the ethos of the undertaken sociallyresponsible actions. To a large extent it is reflected in the ethical dimension.Thus, in enterprises, codes of ethics have become a base of axiology in building ofthe organization cultures. Unfortunately, Polish companies – as shown in the paper– still attach a minor role to the ethical dimension of business.